Dimensi Transendental dalam Penyembuhan Luka Emosional: Analisis Isi Buku “Healing the Emptiness” karya Yasmin Mogahed - Sholahudin, Shofwan Sholahudin; Rahman, Rifal Naufal; Abdurrahman, Maman (Nathiqiyyah, 2025)
This article aims to explore the integration of psychological and Islamic spiritual approaches within a transcendental framework, as conceptualized by Yasmin Mogahed in Healing the Emptiness. Using a qualitative content analysis method, the study investigates the narrative and conceptual structure of the book, particularly in relation to emotional healing. The findings reveal that Mogahed offers a holistic approach that blends biological, psychological, social, and spiritual dimensions, placing the relationship with God as the central foundation of recovery. Her proposed four-step healing process includes diagnosing the root of suffering, removing barriers to healing, treating the wound, and safeguarding the heart. Mogahed also rejects the notion of spiritual bypassing and encourages a conscious integration of spiritual practices and psychological insights. This study concludes that a transcendental approach not only provides a new understanding of emotional healing but also opens up possibilities for more meaningful and spiritually informed psychotherapy, especially in religious contexts.